EDUKASI PEMANFAATAN TOGA DENGAN TOOLS SISTEM INFORMASI OBAL UNTUK SISWA SMK ASTA MITRA GROBOGAN - Purwanjani, Wahyu; Septiarini, Anita Dwi; Suwarni, Sri; Gloria, Fransisca; Akbar, Nanda Dwi; Leki, Karol Giovani Battista (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service activity aims to improve the knowledge and skills of students at SMK Asta Mitra Grobogan in using Family Medicinal Plants (TOGA). The method used is an interactive educational approach, supported by the Natural Medicine Information System (Si-Obal). The activity included lectures, discussions, demonstrations on how to make herbal remedies, educational quizzes, and TOGA planting practices in the school environment. The results of the activity showed that students gained a better understanding of the types of medicinal plants, their benefits, and how to use them to safely treat minor health complaints. The use of Si-Obal as a digital medium was deemed effective and well-received by the students. It is hoped that this activity will contribute to improving health literacy, fostering a caring attitude towards the environment, and encouraging the sustainable use